Principles and strategies for improving the prevention of cardio-metabolic diseases in indigenous populations: An international Delphi study - Stoner, L.; Matheson, A.; Perry, L.; Williams, M.; McManus, Alexandra; Holdaway, M.; Dimer, L.; Joe, J.; Maiorana, Andrew (Elsevier BV, 2017)
The disparity in life expectancy between Indigenous and non-Indigenous populations, including within high-income countries, is driven by a heightened risk of cardio-metabolic diseases. The current study recruited independent panels of experts in Indigenous cardio-metabolic health from Australia, New Zealand and the United States, in order to establish local consensus opinion and initiate dialogue on appropriate prevention strategies. Therefore, a three-round Delphi process was used to consolidate and compare the opinions of 60 experts, 20 from each country. Round one, the experts were asked twelve open-ended questions across six domains: (i) prevention; (ii) consultation; (iii) educational resources; (iv) societal issues; (v) workforce issues; (vi) culture and family. Round two, the experts completed a structured questionnaire based on results from the first round, in which they ranked items according to their importance. Final round, the experts were asked to re-rank the same items after receiving summary feedback about the rank ordering from the previous round. Several themes emerged common to all three countries: (i) socio-economic and education inequalities should be addressed; (ii) educational, behaviour change and prevention strategies should address physical environmental determinants and be responsive to the local context, including being culturally appropriate; and (iii) cultural appropriateness can be achieved through consultation with Indigenous communities, cultural competency training, use of Indigenous health workers, and use of appropriate role models. These findings highlight several key priorities that can be used to initiate dialogue on appropriate prevention strategies. Such strategies should be contextualized to the local Indigenous populations.